Editorial - Farris, Stephen (Toronto journal of theology, 1998)
David Cunningham, in his important essay in this edition of TJT, describes the Trinity as "relationship without remainder." One cannot, of course, apply to essays in a theological journal a description which properly belongs only to the Trinity! Indeed, at first sight, there seems precious little relationship among the contributions to this edition of our journal. The "remainder" is far more clearly in view. This is not a matter of anxiety since TJT, unlike some other theological journals, only occasionally runs theme issues. Still, there does run a certain thread of relationship even through the disparate materials of the present issue.